(untitled) (Journal of Surgical Sciences, 2020)
Background: There are a variety of surgical approaches for correction of ODS, most of these have high recurrence and complication rates. Stapled transanal rectal resection (STARR) was introduced in 2003 by Antonio Longo as a minimally invasive transanal operation for ODS associated with rectocele and or rectal intussusception. Objective: This study was designed to assess the efficacy of Stapled Transanal Rectal Resection (STARR) as a surgical treatment of Obstructed Defecation Syndrome(ODS). Methodology: This is a quasi experimental study that was carried out at Colorectal surgery unit of surgery department in Bangabandhu Sheikh Mujib Medical University. The sample size was 17. The admitted patient of Obstructed Defecation Syndrome with Rectocele and or Rectal intussusception was selected according to inclusion and exclusion criteria. The patient was evaluated by history, clinical examination, proctoscopy, colonoscopy and defecography. Preoperative Longo’s ODS score was determined for each patient and it was compared with postoperative ODS score. Regular follow up was done for each patient at one, three and six months after each operation. Results: Significant improvement of ODS score was observed in 82.35% patients. Only 02 (11.8%) patients didn’t respond to STARR procedure and their postoperative score was 13-15 may be due to coexistence of pelvic floor dysynergy. Postoperative defecatory urgency developed only in 02(11.76%) patients. No patient developed significant postoperative complication like hemorrhage or rectovaginal fistula. Conclusion: STARR is a simple, less invasive and effective procedure for the treatment of ODS due to rectocele and/or rectal intussusception without major morbidity but pelvic floor dyssynergy should be excluded preoperatively because it’s presence makes the surgical intervention fruitless. Journal of Surgical Sciences (2019) Vol. 23(2): 67-70